PENDIDIKAN PENDERITAAN DALAM KITAB AYUB GUNA MEMBERI SOLUSI PERKARA-PERKARA DUNIA PELAYAN TUHAN - Iis Dahlia Mayasari; Chearolina Chearolina; Suryowati Wang (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract: Suffering is pressure that comes from outside a person. The suffering that exists in humans is both unavoidable and inevitable. The problem that arises is: What is meant by suffering education? How to provide a solution to the suffering of people who are complaining? How to provide a solution to the suffering of the quarreling person? How to provide a solution to the suffering of those who commit suicide? How does the education of suffering in the book of Ayub provide solutions to the things of God's servant world at GBI KelIR Samarinda? The answer: (1) Education for suffering is education to live in the world. Humans as God's creation still accept every suffering that comes in their life. (2) The solution to the suffering of a complaining person is: do something happily, have a heart that is willing to accept criticism and suggestions, still give thanks to God, and be humble. (3) The solution to the suffering of the quarreling person is: don't always feel right, apologize first when you are guilty, learn to yield, and be willing to listen to advice. (4) The solution to the suffering of a person who commits suicide is someone who dares to live in pain and can accept the reality of life, is obedient to God, is always grateful, and always longs to live in historical peace. (5) The education of suffering taught to God's servants at GBI KelIR Samarinda is: Education continues to survive, Education to Realize God is the Source of Life, Education Do not Blame Anyone, and Education